Implementasi Relaksasi Genggam Jari Dan Nafas Dalam Untuk Menurunkan Tekanan Darah Pada Pasien Congestive Heart Failure (Chf) - Syipa Audia Nurpadilah; Syaukia Adini; Ida Rosdiana; Asep Riyana (MEJORA Medical Journal Awatara, 2025)
Congestive heart failure (CHF) is one of the non-communicable diseases caused by structural or functional impairment of the heart. In Indonesia, the highest number of CHF cases is reported in West Java Province, with 186,809 cases. Inadequate management of CHF may lead to serious complications; therefore, blood pressure control is an essential component in preventing such complications. In addition to pharmacological therapy, blood pressure management can be supported by non-pharmacological interventions, one of which is finger-holding relaxation combined with deep breathing. This relaxation technique works by reducing sympathetic nervous system activity and promoting a relaxation response. This study aimed to describe the implementation of finger-holding relaxation and deep breathing therapy in reducing blood pressure among patients with CHF. A qualitative method with a case study approach was used. The study was conducted at Pandega Regional Hospital, Pangandaran, from April 8 to April 28, 2025, involving two CHF patients with a nursing diagnosis of ineffective peripheral perfusion. The intervention was administered for three consecutive days. The results showed a decrease in blood pressure in both patients after the implementation of finger-holding relaxation and deep breathing therapy. Systolic blood pressure decreased by 40 mmHg in the first patient and by 55 mmHg in the second patient, while diastolic blood pressure decreased by 25 mmHg and 30 mmHg, respectively. These findings indicate that finger-holding relaxation and deep breathing therapy can help reduce blood pressure in patients with CHF and a history of hypertension and may be used as a complementary therapy alongside pharmacological treatment.